Studies on the Mechanism of Transduction by Bacteriophage ϕ_entitystart_#947_entit I. Genetic Characterization of the Transducing Segment - Gratia, Jean-Pierre (1976)
The bacteriophage Φγ, though related to the lambdoid phage ϕ80, has unusual features in its specialized transduction and is being investigated to determine the mechanism of the transduction process. Genetic analysis of the transducing element gives evidence for a relatively long and uniform linear segment, up to about 1% of the E. coli chromosome, extending in either direction from the prophage attachment site, e.g., on the right side: att80-tonB-trpABCDE-cysB-pryF. The att end includes a variable amount of phage genome, probably very short in most particles. In a small fraction of the transducing particles the phage segment may be more extensive and, conversely, the bacterial segment is shorter, ending around cysB. The transducing segment from modificationless bacteria carries a site susceptible to the K-restriction system which affects the efficiency of transduction.